Characterization of bacteria isolated from fermented food and evaluation of their potential to be probiotic - Archi, Shucheta Nazia; Tabassum, Nafisa; Juhana, Juairiah Bakth (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.